Lung function trajectories in health and disease - Agusti, Alvar; Faner, Rosa (The lancet respiratory medicine, 2019)
The normal lung function trajectory from birth to death has three phases: a growth phase (from birth to early adulthood), a plateau phase (that lasts for a few years), and a decline phase resulting from physiological lung ageing. Numerous genetic and environmental factors can alter one or more of these phases. Evidence shows that several lung function trajectories exist throughout the life course and, importantly, that some of them are associated with substantial implications for health and disease. Here, we review the evidence, formulate a series of questions, and identify various challenges that need to be addressed to identify potential opportunities to promote respiratory health.